Rise and shine: The use of polychromatic short‐wavelength‐enriched light to mitigate sleep inertia at night following awakening from slow‐wave sleep. (31st January 2022) - Hilditch, Cassie J.; Wong, Lily R.; Bathurst, Nicholas G.; Feick, Nathan H.; Pradhan, Sean; Santamaria, Amanda; Shattuck, Nita L.; Flynn‐Evans, Erin E.
Summary: Sleep inertia is the brief period of performance impairment and reduced alertness experienced after waking, especially from slow‐wave sleep. We assessed the efficacy of polychromatic short‐wavelength‐enriched light to improve vigilant attention, alertness and mood immediately after waking from slow‐wave sleep at night. Twelve participants (six female, 23.3 ± 4.2 years) maintained an actigraphy‐confirmed sleep schedule of 8.5 hr for 5 nights, and 5 hr for 1 night prior to an overnight laboratory visit. In the laboratory, participants were awakened from slow‐wave sleep, and immediately exposed to either dim, red ambient light (control) or polychromatic short‐wavelength‐enriched light (light) for 1 hr in a randomized crossover design. They completed a 5‐min Psychomotor Vigilance Task, the Karolinska Sleepiness Scale, and Visual Analogue Scales of mood at 2, 17, 32 and 47 min after waking. Following this testing period, lights were turned off and participants returned to sleep. They were awakened from their subsequent slow‐wave sleep period and received the opposite condition. Compared with the control condition, participants exposed to light had fewer Psychomotor Vigilance Task lapses ( χ 2 [1] = 5.285, p  = 0.022), reported feeling more alert (Karolinska Sleepiness Scale: F 1, 77  = 4.955, p  = 0.029; Visual Analogue Scalealert : F 1, 77  = 8.226, p  = 0.005), and reported improved mood (Visual Analogue Scalecheerful : F 1, 77  = 8.615, p  = 0.004). There was no significant difference in sleep‐onset latency between conditions following the testing period ( t 10  = 1.024, p  = 0.330). Our results suggest that exposure to polychromatic short‐wavelength‐enriched light immediately after waking from slow‐wave sleep at night may help improve vigilant attention, subjective alertness, and mood. Future studies should explore the potential mechanisms of this countermeasure and its efficacy in real‐world environments.